Mental Health on University Campuses and the Needs of Students They Seek to Serve - Goodman, Leah (Building Healthy Academic Communities Journal, 2017)
Background: The mental health of college students in the U.S. has become an undeniable concern to university administrators, service providers, and the higher education community at large. While universities seek to educate future great minds, their current policies and infrastructure do not unanimously prioritize mental health, thus, they often cannot meet the holistic needs of students and struggle to uphold their central mission. Aim: To outline the literature surrounding mental health in postsecondary education and the holistic needs of university students in order to target the national discussion of mental health toward actionable system change. Methods: A comprehensive review of the literature on college student mental health in the U.S. Results: The literature demonstrates that policy change is necessary to fully support students with psychiatric disabilities and mental health concerns. Conclusions: Mental health is a critical issue for young adults, and college presents a prime developmental context to equip students with the skills for a lifetime of mental health and wellbeing. Further research is needed to explore the impact of implementing innovative programs, curricular changes and supported education programs to support college students.